Meningkatkan Hasil Belajar Pak Dengan Model Pbl Siswa Fase B Kelas 4 SD Negeri Kestalan Surakarta - Margareta Nataria (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education (PAK) for 4th-grade students at SDN Kestalan Surakarta using a Problem-Based Learning (PBL) model. The research was conducted in two cycles involving Phase B students. The results indicated a significant improvement in both cognitive learning outcomes and collaborative attitudes. In the first cycle, 33% of students achieved a "proficient" level, which increased to 83% in the second cycle. Additionally, the aspect of collaboration increased from an average of 55% in the first cycle to 84% in the second. These findings suggest that implementing the PBL model not only enhances students' understanding of PAK material but also fosters stronger collaborative skills. Thus, the PBL model can serve as an effective alternative to improve both learning outcomes and character development among students.